ECONOMIC ANALYSIS OF DIGITALIZATION IN IMPROVING ENERGY RESOURCE EFFICIENCY IN REGIONS (Marketing Journal, 2025)
The energy sector is one of the main sectors of the economy and is of great importance for the development of regions. However, the need for effective management of energy resources, their optimal use, and the utilization of economical resources is increas ing. This issue is relevant not only from an ecological perspective but also economically, and the introduction of digital technologies creates new opportunities in energy resource management. The study focuses on the economic analysis of digitization in i mproving the efficiency of energy resources in regions, examining its potential, benefits, and opportunities, as well as the challenges in implementation. 285
Keywords: efficiency of energy resources; modernization of energy resources; innovative development; cost minimization; efficiency assessment; optimization; clustering